Analisis Perkiraan Jumlah Pegawai Negeri Sipil di Kota Medan Menggunakan Metode Single Exponential Smoothing - Riska Maria Br. Purba; Desriana Aritonang; Grace Theodora Valentina Purba; Kevin Yohanes Hutauruk; Stevanus Hendy Sitanggang; Indra M. Sarkis S. (Universitas Methodist Indonesia, 2024)
The number of civil servants is a crucial factor in determining budget allocation, human resource planning and the provision of public services. In Medan City, the number of civil servants has decreased from year to year based on data from the North Sumatra Province Central Statistics Agency. The uncertainty of the number of civil servants from year to year makes forecasting the number of civil servants a challenging task and requires appropriate analytical methods. Therefore, an analysis of the estimated number of civil servants is needed to determine the right policy. One method that can be used is Single Exponential Smoothing (SES). Based on the results of testing predictions for the number of civil servants in the city of Medan for the 2023 period using alpha SES of α0.1, α0.3, α0.5, α0.7 and α0.9, it was found that using alpha 0.7 gave prediction results with a Mean Square Error value the smallest is 26515890 and the predicted number of civil servants is 11867 people in 2023. The prediction results can be used by local governments to plan human resource needs, including recruitment, training or development of civil servants according to future needs.